Clean Money: Picking Winners in the Green Tech Boom - Rubino John (Wiley, 2008)
In Clean Money, John Rubino, Editor of GreenStockInvesting.com, introduces you to the world of clean tech (also known as green tech) and its wealth creation potential. Throughout the book, he explores a variety of clean energy sources–from solar power to biofuels–and shows how these renewable resources will spawn successful companies and rising share prices. Page by page, you'll discover the technologies that will drive this boom and become familiar with the state of their markets, their growth prospects, and the companies that are best positioned to become tomorrow's success stories.